The Influence of Concert Promotion Through Instagram on Interest in Purchasing Music Concert Tickets Post Covid-19 Pandemic - Alvito Rangga Pradipta; Ar Razi Lincoln (Cakra Communico: Journal of Communication Science, 2024)
In the era of globalization and technological development, social media has become an integral part of people's daily lives. One of the most popular social media platforms today is Instagram. Instagram is not only a place to share personal moments, but also an effective means of promoting and marketing various events, including music concerts. This study aims to investigate and analyze the effect of music concert promotion through Instagram on interest in purchasing music concert tickets after the COVID-19 pandemic. Although several previous studies have examined the role of social media in promoting concerts, there are still gaps in previous research. To understand the impact of Instagram social media on concert promotion, this study will explore the impact of concert promotion through Instagram on concert ticket purchase preferences by applying applied theory, namely AIDA theory (Attention, Interest, Desire, Action) which is closely related to marketing. This research uses a quasi-experiment method. The main finding of this study is that there is no significant influence between the use of Instagram social media as a music concert promotion tool and the interest in purchasing music concert tickets after the COVID-19 pandemic. It was found that the experimental group that received the intervention of concert promotion shows through Instagram had a higher score of interest in purchasing music concert tickets (mean score 37.93) compared to the control group that did not receive the intervention (mean score 32.20). Although the difference was not statistically significant, this higher score shows the tendency that promotional impressions can positively influence the interest in purchasing tickets.